Measuring The Impact Of The Bali Bombing As An Economic Shock: A Difference-In-Differences Method Approach With Interaction Variable - Wicaksana, Arif Kurnia; Fatoni, Erma Ziamah (Convergence: The Journal of Economic Development, 2025)
Abstract This study investigates the economic consequences of terrorism by examining the impact of the Bali Bombings I (2002) and II (2005) on individual income in Indonesia. Using microdata from the Indonesia Family Life Survey (IFLS) for the periods 2000 and 2006, the analysis applies the Difference-in-Differences (DiD) method to identify causal effects of the bombings on income outcomes. The empirical strategy distinguishes between pre- and post-bombing periods, affected and unaffected regions, and further introduces interaction variables capturing direct impacts on individuals experiencing material and psychological losses. Additional socio-economic controls, such as education, gender, age, employment status, household role, urban–rural residence, ethnicity, and welfare status, are incorporated to reduce estimation bias. The results show that the Bali Bombings significantly reduced average income in affected areas by approximately 26.44 percent compared to unaffected regions. Individuals directly exposed to the bombings experienced even larger losses, with their income declining by about 36.33 percent. Distributional analysis further indicates that the middle-income group (40 percent of the population) was most severely affected, while low- and high-income groups showed relatively minor impacts. These findings highlight the vulnerability of the middle class, which plays a critical role in sustaining Indonesia’s economic development. This study contributes to the literature on terrorism and economic development by providing micro-level evidence of how external shocks disrupt household welfare and income distribution. The findings have important policy implications, particularly for designing social protection programs and resilience strategies in tourism-dependent regions facing risks of conflict and disaster. Keywords : Difference-in-Differences, Individual Income, Bali Bombings, Direct Impact, Education and Age, Household Welfare, Terrorism and Economy.   Abstrak Penelitian ini mengkaji dampak ekonomi dari peristiwa terorisme dengan meneliti pengaruh Bom Bali I (2002) dan Bom Bali II (2005) terhadap pendapatan individu di Indonesia. Data yang digunakan berasal dari Indonesia Family Life Survey (IFLS) periode 2000 dan 2006. Metode yang digunakan adalah Difference-in-Differences (DiD) untuk mengidentifikasi pengaruh kausal dari peristiwa bom terhadap pendapatan. Strategi empiris membedakan antara periode sebelum dan sesudah bom, wilayah terdampak dan tidak terdampak, serta menambahkan variabel interaksi untuk menangkap dampak langsung pada individu yang mengalami kerugian material maupun psikologis. Variabel kontrol sosio-ekonomi juga dimasukkan, seperti pendidikan, gender, usia, status pekerjaan, peran dalam rumah tangga, lokasi perkotaan/pedesaan, etnisitas, dan status kesejahteraan. Hasil penelitian menunjukkan bahwa Bom Bali secara signifikan menurunkan rata-rata pendapatan di daerah terdampak sekitar 26,44 persen dibandingkan daerah yang tidak terdampak. Individu yang terkena dampak langsung mengalami kerugian lebih besar, dengan penurunan pendapatan sekitar 36,33 persen. Analisis distribusi pendapatan menunjukkan bahwa kelompok berpendapatan menengah (40 persen dari populasi) adalah yang paling terdampak, sementara kelompok rendah dan tinggi relatif tidak terlalu terkena dampaknya. Temuan ini menyoroti kerentanan kelas menengah, yang justru memiliki peran penting dalam mendorong pembangunan ekonomi Indonesia. Penelitian ini memberikan kontribusi pada literatur tentang terorisme dan pembangunan ekonomi dengan bukti mikro mengenai bagaimana guncangan eksternal mengganggu kesejahteraan rumah tangga dan distribusi pendapatan. Temuan ini juga penting bagi perumusan kebijakan, terutama untuk merancang program perlindungan sosial dan strategi ketahanan di wilayah yang bergantung pada pariwisata serta berisiko terhadap konflik maupun bencana. Kata kunci: Difference-in-Differences, Pendapatan Individu, Bom Bali, Dampak Langsung, Pendidikan dan Usia, Kesejahteraan Rumah Tangga, Terorisme dan Ekonomi.